Flavonoids from the leaves of Iranian Linden; Tilia rubra subsp. caucasica - M.R. Delnavazi; M. Shahabi; N. Yassa (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Plants belonging to the genus Tilia L. (Tiliaceae) are often tall beautiful trees which are considered for various medicinal potentials of their flowers and leaves. The present study was an attempt to investigate the phytochemical constituents of Tilia rubra subsp. caucasica leaves from the hyrcanian forests of north of Iran. Methods: Chromatography on Silica gel (normal and reversed-phase) and Sephadex LH20 was applied for isolation and purification of the compounds from the hydroalcoholic extract of the plant leaves. The structures of isolated compounds were elucidated using UV, 1H-NMR and 13C-NMR spectral analyses. Results: Four flavonoid glycosides, quercetin-3-O-β-D-glucoside-7-O-α-L-rhamnoside (petiolaroside), quercetin-3-O-α-L-rhamnoside (quercitrin), apigenin-7-O-β-D-glucoside (cosmosiin) and luteolin-7-O-β-D-glucoside (cynaroside) were isolated from T. rubra subsp. caucasica leaves, which have been previously documented for their various biological activities. Conclusion: The results of this study introduc T. rubra subsp. caucasica as a source of bioactive flavonoid glycosides and highlight it as an appropriate option for further pharmacognostical studies.